Health Care Provider Surveys in the United States, 2000–2010: A Review. (March 2013) - McLeod, Caroline C.; Klabunde, Carrie N.; Willis, Gordon B.; Stark, Debra
Surveys of health care providers (e.g., physicians and other health care professionals) are an important tool for assessing health care practices and the settings in which care is delivered. Although multiple methods are used to increase survey data quality, little is known about which methods are most commonly implemented. We reviewed 117 large surveys described in literature published between 2000 and 2010, examining descriptions of survey design features, survey implementation, and response rates. Despite wide variation, the typical provider survey selected practicing physicians as respondents, used the American Medical Association Masterfile as sample frame, included mail as both mode of initial contact and questionnaire administration mode, and offered monetary incentives to respondents. Our review revealed inconsistency of documentation concerning procedures used, and a variety of response rate calculation methods, such that it was difficult to determine practices that maximize response rate. We recommend that reports provide more comprehensive documentation concerning key methodological features to improve assessment of survey data quality.